2020
DOI: 10.1001/jamanetworkopen.2019.19706
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Trends Associated With Mortality Among Adults With Hip Fracture in Singapore

Abstract: IMPORTANCE Examining trends in mortality following hip fracture and its associated factors is important for population health surveillance and for developing preventive interventions. OBJECTIVE To examine temporal trends in, and risk factors associated with, mortality following hip fracture over 18 years in Singapore. DESIGN, SETTING, AND PARTICIPANTS This retrospective, population-based cohort study included men and women aged 50 years and older admitted to Singapore hospitals for first hip fracture identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…Most of the deaths reported at 2 years follow up were associated with co-morbidities and higher ASA grade, which is in line with other studies (Hommel et al, 2008) [ Table 9]. Young E-L et al, in his study "Risk Factors and Trends Associated with Mortality Among Adults with Hip Fracture in Singapore" followed 36082 patients for 18 years after hip fractures and con-cluded that Malay ethnicity, older age, male sex, prefracture co-morbidity, and trochanteric fractures were independently associated with increased risk of death, identifying population groups that could be targeted for intervention strategies (Yong et al, 2020). These results are in line with our study in which 8 deaths reported at the end of 3 years follow up were associated with higher age (>70 years), male sex, pre-fracture co-morbidities and higher ASA grades [ Table 8].…”
Section: Hypertensionsupporting
confidence: 81%
“…Most of the deaths reported at 2 years follow up were associated with co-morbidities and higher ASA grade, which is in line with other studies (Hommel et al, 2008) [ Table 9]. Young E-L et al, in his study "Risk Factors and Trends Associated with Mortality Among Adults with Hip Fracture in Singapore" followed 36082 patients for 18 years after hip fractures and con-cluded that Malay ethnicity, older age, male sex, prefracture co-morbidity, and trochanteric fractures were independently associated with increased risk of death, identifying population groups that could be targeted for intervention strategies (Yong et al, 2020). These results are in line with our study in which 8 deaths reported at the end of 3 years follow up were associated with higher age (>70 years), male sex, pre-fracture co-morbidities and higher ASA grades [ Table 8].…”
Section: Hypertensionsupporting
confidence: 81%
“…Male sex, older age, and higher CCI have all been associated with increased mortality after geriatric hip fracture. [18][19][20] So, it was not surprising that our mortality rate was also male dominant. This may be related to the predominance of males affected by In this cohort of patients, C+ and Cs patients experienced a greater overall major complication rate, including an increase in complications such as sepsis, pneumonia, acute respiratory failure, cardiac arrest, and inpatient mortality.…”
Section: Discussionmentioning
confidence: 85%
“…The variables constituting the tool have been reported as risk factors for severe COVID-19 illness or mortality, are constituents of other well validated prognostic tools such as the Charlson Comorbidity Index (CCI), or are mortality predictors for other respiratory illnesses [26][27][28][29][30][31][32][33][34][35]. Older age in particular heralds worse outcomes in COVID-19 patients in an incremental [26,30,32,34,35].…”
Section: Discussionmentioning
confidence: 99%